2021
DOI: 10.1530/raf-21-0053
|View full text |Cite
|
Sign up to set email alerts
|

Nonhormonal therapy for endometriosis based on energy metabolism regulation

Abstract: Objectives: Ovarian function suppression is the current pharmacotherapy of endometriosis with limited benefit and adverse effects. New therapeutic strategies other than hormonal therapy are developed based on the molecular mechanisms involved in the hypoxic and oxidative stress environments and metabolism unique to endometriosis. Methods: A literature search was performed between January 2000 and March 2021 in the PubMed database using a combination of specific terms. Results: Endometriosis-associated metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 90 publications
(242 reference statements)
3
29
0
Order By: Relevance
“…Endometriotic cells convert significant amounts of glucose into energy to undergo growth in hypoxic milieus. 7 Recent studies suggest that reprogramming of energy metabolism is a hallmark of endometriosis development. 6 , 11 , 12 , 13 First, we focus on how endometriotic cells dynamically reconstruct signaling pathways that regulate glucose metabolism in the maintenance of energy homeostasis and summarize the underlying key regulators.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Endometriotic cells convert significant amounts of glucose into energy to undergo growth in hypoxic milieus. 7 Recent studies suggest that reprogramming of energy metabolism is a hallmark of endometriosis development. 6 , 11 , 12 , 13 First, we focus on how endometriotic cells dynamically reconstruct signaling pathways that regulate glucose metabolism in the maintenance of energy homeostasis and summarize the underlying key regulators.…”
Section: Resultsmentioning
confidence: 99%
“…Changing environmental conditions are reported to accelerate a cellular metabolic switch from glycolysis to mitochondrial oxidative phosphorylation or vice versa. 7 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A review by Viganò et al (2012) showed that BMI is reduced in women with endometriosis [ 5 ]. A possibility of non-hormonal therapy of endometriosis based on the regulation of energy metabolism is being studied [ 6 , 7 ]. However, the factors of energy metabolism in PF and their role in the development of endometriosis remain underestimated.…”
Section: Introductionmentioning
confidence: 99%